Organic micropollutants in groundwater of India—A review. (15th October 2019) - Sackaria, Merin; Elango, Lakshmanan
Abstract: Groundwater pollution due to organic micropollutants is a major cause of concern, especially in parts of the world where available water resources are on the decline. India is the largest user of groundwater where the presence of micropollutants in the subsurface environment has been the focus of many researchers. The objective of this study was to provide a detailed review of studies on micropollutants in Indian groundwater and to provide strategies for further work. It is found that the presence of pharmaceuticals, endocrine disrupting compounds, surfactants, phthalates, per‐ and poly‐fluoroalkyl substances, personal care products, artificial sweeteners, and pesticides in groundwater from different parts of India is reported. Pesticides and phthalate concentrations reported exceed the standard guideline values. This review points out the regions where the groundwater is prone to contamination due to micropollutants. An assessment of temporal variation in the concentration of micropollutants in groundwater has been done only by a few researchers. This study highlighted the need for more research on the possible presence of micropollutants in groundwater, especially in the major polluted rivers in cities where more pharmaceuticals, pesticides, and plastic industries are located. Practitioner Points: Organic micropollutants were not new contaminants into the environment but the one entered even decades ago which has threatening effect. The number of studies on organic micropollutants in groundwater is lesser than surface water or wastewater. Scarcity on the studies of micropollutants was a result of definite technical lack in its analysis and complexity in sample preparation. Most of the studies done were related to contamination sites and point sources. Abstract : Sources of organic micropollutants for groundwater contamination.